Jeremy, the English garden snail : heredity, citizen science, and #snaillove - Pattison, Darcy (Pattison, Darcy. Another extraordinary animal., 2025)
"In a charming garden of London, a tiny hero emerges -- Jeremy, a garden snail with a remarkable difference. Most snail shells coil right, but Jeremy's shell spirals to the left, making him a one-in-a-million wonder. That small difference will catapult him to fame, as scientists and snail enthusiasts rally to help him find a mate. Written by award-winning author Darcy Pattison and beautifully illustrated by Olga Gonina, this engaging story follows Jeremy's journey from a humble compost heap to international stardom. When Dr. Angus Davison, a geneticist at the University of Nottingham, learns about Jeremy, he sees an opportunity to unravel the mysteries of genetics and body symmetry. But there's a snail-sized problem -- Jeremy needs a left-coiled partner to mate with! What follows is a heartwarming tale of citizen science, as Dr. Davison launches the #snaillove campaign, reaching out to people worldwide to help find Jeremy a mate. This book is more than just a cute story about a snail looking for love. It's an elementary introduction to the world of heredity, inheritance, and scientific research, all wrapped up in an accessible story."--Amazon.com.